Fracture characteristics of slag-based geopolymer mortars with recycled aggregates under mode I and mode II Loading - Poleboyana Rohit; T. D. Gunneswara Rao; M. Chandrasekhar (Journal of Engineering and Applied Science)
Abstract This study investigates the fracture characteristics of slag-based geopolymer mortars (SGPM) incorporating recycled fine aggregates (RFA) from construction demolition waste. The research examines both tensile (mode I) and shear (mode II) fracture behaviors, analyzing the effects of different notch-to-depth ratios (0.20, 0.25, 0.30) and varying RFA replacement levels (10%, 20%, 30%, 40%). The experimental results reveal that increasing notch-to-depth ratios leads to increased brittleness, reducing fracture energy in both modes. Higher RFA levels further decrease overall strength and fracture energy, with a more significant impact on mode II. Mode II fracture energy is notably higher, approximately 23 times greater than mode I. The findings highlight the importance of balancing notch-to-depth ratios and RFA content to optimize SGPM’s mechanical performance for sustainable construction applications. This study concludes that while SGPM with RFA offers environmental benefits, careful consideration of RFA proportions and notch-to-depth ratios is crucial to maintain desired structural properties.